Introduction to Traditional Houses Using Augmented Reality Based on Unity 3D on Android Platform - Rizky Bagas Prasetyo, Achmad; Dijaya, Rohman (International Journal on Human-Computing Studies, 2025)
Indonesian culture is rich with traditional houses spread across the archip elago, serving not only as physical structures but also as symbols of history and cultural identity. Each traditional house has unique characteristics that reflect local wisdom and traditional life. However, modernization and urbanization threaten the continuity of many traditional houses, compounded by the lack of public appreciation for traditional cultural values. An innovative approach is needed to address these challenges, one of which is leveraging augmented reality (AR) technology. AR allows users to interact with virtual objects in the real world through electronic devices such as smartphones. AR technology, using Surface Tracking and visual inertial odometry (VIO), can be used to introduce and preserve traditional houses. This study, titled "Introduction to Traditional Houses Based on Augmented Reality Using Unity 3D on the Android Platform," employs the Extreme Programming (XP) method. XP is suitable for small teams that require rapid adaptation to changes, aiming to create high-quality software and enhance productivity.